The story of Maroochy - McBurney, Yvonne, 1925- (Strathfield, N.S.W. : Educational Material Aid, 1979)
Legend about Wallum used as upper primary reader; making of various land marks.
Keywords: English language. Reading books. Secondary school texts; Readers; Sites - Dreaming tracks; Education - Indigenous studies - Primary - Curriculum; Stories and motifs; Maroochy River / Maroochydore (SE Qld SG56-10)